The research of antimicrobial and wound healing activity of artemisia siversania essential oil (Experimental biology, 2015)
The article examines biological peculiarities of Artemisia siversiana essential oil. It was found that Artemisia siversiana essential oil has mild antibacterial effect on gram-positive microorganisms. The range of it’s antimicrobial effect includes antifungal effect on yeast fungus Candida albicans. It means that applicability and prospects of this preparation are beyond question and require further research
Keywords: The article examines biological peculiarities of Artemisia siversiana essential oil. It was found that Artemisia siversiana essential oil has mild antibacterial effect on gram-positive microorganisms. The range of it’s antimicrobial effect includes antifu